A study on cutaneous adverse drug reactions at district Mc. Gann teaching hospital, Shimoga institute of medical sciences, Shivamogga, Karnataka, India - Murray, Jean Lourdes; H., Vedavathi; Prasad, Nagaraja S.; HJ, Dadapeer; Revankar, Shreenivas P. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Adverse drug reactions very often manifest in the form of cutaneous reactions. Majority of new drugs are developed by western countries and releases the drug worldwide after testing on small number of patients. Safety profile of such drugs may not be relevant in our country due to varied factors. Pharmacovigilance in the form of post-marketing surveillance helps to establish the accurate safety profile of drugs. The objective of this study was to study the various cutaneous adverse drug reactions (CADRs), frequency, type, severity and preventability of CADRs and to evaluate the drugs causing the CADRs. Methods: A total of 52 patients were recruited for this study which was conducted in the dermatology OPD department from November 2015 to April 2016, demographic details, causality, severity, preventability were analysed by using standard scales. Results: 52 patients with CADRs were included in the study during the 6 months study period. Results were presented in the form of number and percentage. Most common age group with CADRs was 40- 60 years; the most common suspected drug group causing CADRs was antimicrobials 46.15%. According to Naranjos scale 67.30% of CADRs were probably caused by drugs. Schumoch and Thornton scale showed that 63.46% of CADRs in the study were definitely preventable. Conclusions: Wide variety of drugs causes CADRs. Awareness among clinicians is required for active reporting of CADRs. Patients need to be educated for the cautious use of drugs causing ADRs to prevent the same.